Curable resin composition, insulating cured film obtained by curing the composition, insulating cured film for touch panel, and touch panel
The curable resin composition, featuring an alkali-soluble resin with specific structural units and a photoreactive monomer, addresses adhesion, chemical resistance, and wrinkle issues in touch panels and liquid crystal display devices, resulting in improved performance and productivity.
Patent Information
- Application Number
- JP2021526149
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-06-14
- Filing Date
- 2020-06-12
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2040-06-12
AI Technical Summary
Existing curable resin compositions used in touch panels and liquid crystal display devices face challenges with adhesion to ITO films, chemical resistance, and wrinkle resistance, particularly during heat treatment.
A curable resin composition comprising an alkali-soluble resin with specific structural units, a photoreactive monomer, and a photopolymerization initiator, which forms a cured film with enhanced chemical resistance, development properties, and wrinkle resistance.
The composition achieves excellent adhesion to glass substrates and ITO films, maintains chemical resistance against manufacturing chemicals, and minimizes wrinkle formation on the surface, thereby improving the productivity and performance of touch panels.
Smart Images

Figure 0007660504000016 
Figure 0007660504000017 
Figure 0007660504000018
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable resin composition and an insulating cured film obtained by curing the composition. The present invention relates to a curable resin composition that is useful for insulating cured film applications (for example, insulating film applications, protective film applications, flat film applications, etc.) used in touch panels and the like, an insulating cured film for touch panels obtained by curing the composition, and a touch panel including the cured film. [Background technology]
[0002] In recent years, as electronic devices have become more functional, diversified, and smaller and lighter, an increasing number of devices are equipped with transparent touch panels on the front of display elements such as liquid crystal displays, through which characters, symbols, pictures, and the like displayed on the display elements can be viewed and selected, and the functions of the devices can be switched by operating the transparent touch panel.
[0003] There are several types of touch panel detection methods, including resistive, capacitive, ultrasonic, and optical, with resistive and capacitive methods becoming more common in recent years. For example, the resistive film method is a two-sided structure consisting of an upper electrode film and a lower electrode glass, and the switch is pressed and responds when pressure is applied from above the upper electrode film with the tip of a pen or similar. The capacitive method is a method consisting of a protective glass on the surface and a sensor glass, and when a finger touches the glass on the surface, electrostatic bonding occurs, creating a difference in electrostatic capacitance with the glass behind, and the touched point is determined from this difference.
[0004] Capacitive touch panels use, for example, glass with an ITO film as a substrate, and provide an insulating film or a protective film in a laminated structure to prevent erroneous recognition of the touched position. Such protective films include those made of highly hard inorganic SiO2, SiNx, transparent resins, etc., and organic protective films. Known organic protective film materials include, for example, UV-curable coating compositions containing polymerizable group-containing oligomers, monomers, photopolymerization initiators, and other additives (see, for example, Patent Document 1).
[0005] In addition, when combined with a liquid crystal display device, touch panels can be classified into out-cell structure, on-cell structure, and in-cell structure depending on the installation location. In recent years, on-cell structure and in-cell structure, which have excellent visibility, are becoming mainstream. In these on-cell structure and in-cell structure, the touch panel is incorporated into the liquid crystal panel. Furthermore, as touch panel structures, a two-sided type in which an X electrode is arranged on one side of an insulating film and a Y electrode is arranged on the other side, and a one-sided type in which an X electrode and a Y electrode are formed on the same plane are known. In this one-sided touch panel structure, electrodes are separated by an insulating film, and the separated electrodes are electrically connected to each other by a member called a jumper part (for example, see Patent Documents 2 and 3). As such a jumper part, for example, one having an ITO film is known.
[0006] Furthermore, insulating films are also used in liquid crystal display devices and the like, and many known materials used for insulating films include photosensitive resin materials for insulating films that contain, for example, alkali-soluble resins, photocurable monomers, and photopolymerization initiators (see, for example, Patent Documents 4 and 5). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2010-027033 A [Patent Document 2] JP 2017-41204 A [Patent Document 3] JP 2012-88836 A [Patent Document 4] JP 2017-173525 A [Patent Document 5] JP 2017-173526 A Summary of the Invention [Problem to be solved by the invention]
[0008] As described above, curable resin compositions are often used to form insulating films used in touch panels, liquid crystal display devices, etc. Such insulating films are required to have adhesion to an ITO film (electrode). For example, the adhesion to the ITO film is required to be such that the adhesive strength between the insulating film and the ITO film is not likely to decrease due to chemicals used in the manufacturing process (excellent "chemical resistance").
[0009] In addition, for example, when a touch panel is manufactured using a curable resin composition, an insulating film or the like is formed by applying the curable resin composition onto a substrate by lithography technology or the like, exposing and developing the composition. At this time, a coating film of the curable resin composition is formed once on a substrate such as a glass substrate, and then the coating film corresponding to the non-patterned portion may be removed by a developer. When a metal thin film or ITO film containing Al or Mo is formed by PVD or the like after the exposure and development of the curable resin composition, the metal thin film or ITO film is deposited directly on the substrate from which the coating film of the curable resin composition has been removed. However, in such a case, the adhesion between the glass substrate and the ITO film or metal thin film may decrease. For this reason, when an insulating film or the like is formed using a curable resin composition, it is also required that the adhesion between the glass substrate and the ITO film or metal thin film such as Al or Mo after the insulating cured film is removed after patterning (development) is excellent (excellent "developability").
[0010] Furthermore, when an insulating film formed using a curable resin composition is subjected to heat treatment or the like after an ITO film is formed on the insulating film, fine wrinkles may occur on the contact surface between the ITO film and the insulating film. It has been found that the occurrence of fine wrinkles in an insulating film affects various physical properties such as the transparency of the insulating film. For this reason, there is a demand for the development of a curable resin composition that is excellent in the above-mentioned chemical resistance and developability, and that, when used as an insulating film, causes fewer wrinkles on the contact surface with the ITO film, which are thought to be mainly caused by the formation of the ITO film and the subsequent heat treatment or the like (excellent in "wrinkle resistance").
[0011] In order to solve the above-mentioned problems, the present invention aims to provide a curable resin composition capable of forming a cured film having excellent chemical resistance, developability, and wrinkle resistance, an insulating cured film and an insulating cured film for touch panels obtained by curing the composition, and a touch panel including the cured film. [Means for solving the problem]
[0012] The present inventors have conducted extensive research to solve the above problems, and as a result, have found that the above problems can be solved by using a composition containing a copolymer having a specific structure and a monomer having a specific structure, thereby completing the present invention. <1> A curable resin composition comprising: an alkali-soluble resin (A) which is a copolymer containing a structural unit (a-1) derived from a compound represented by the following formula (a-1α) and at least one selected from unsaturated carboxylic acids having a cyclic skeleton; a structural unit (a-2) having a glass transition temperature of 70 to 200°C when made into a homopolymer; and a structural unit (a-3) derived from an unsaturated compound containing an epoxy group; a photoreactive monomer (B) represented by the following formula (b-1); and a photopolymerization initiator (C). [ka] (In the formula, R 1 ~R 3 each independently represents a hydrogen atom, a methyl group, or a carboxy group; X 1 represents a straight-chain or cyclic aliphatic hydrocarbon group having 1 to 15 carbon atoms which may contain a single bond or an oxygen atom. [ka] (In formula (b-1), R 13 ~R 14 each independently represents a hydrogen atom or a methyl group; Y 1 ~Y 2 each independently represents a single bond or a linear or branched aliphatic hydrocarbon group having 1 to 6 carbon atoms; X 2represents an aliphatic hydrocarbon group or an aromatic group having a cyclic skeleton. <2> The structural unit (a-2) is derived from at least one compound selected from the group consisting of a compound represented by the following formula (a-2α) and a compound represented by the following formula (a-2β): <1> The curable resin composition according to claim 1. [ka] (In formula (a-2α), R 4 ~R 6 each independently represents a hydrogen atom or a methyl group; R 7 represents a linear, branched or cyclic aliphatic hydrocarbon group having 1 to 12 carbon atoms, or an aromatic group having 6 to 20 carbon atoms. 8 ~R 12 each independently represents a hydrogen atom, a methyl group, an acetyl group, a benzoyl group, an isopropyl group, a tert-butyl group, or a sec-butyl group. <3> The content of the photoreactive monomer (B) relative to the total amount of the photoreactive monomers in the curable resin composition is 75 mass% or more. <1> or the above <2> The curable resin composition according to claim 1. <4> The weight average molecular weight of the alkali-soluble resin (A) is 5,000 to 20,000. <1> ~The above <3> The curable resin composition according to any one of the preceding claims. <5> The content (mol %) of the structural unit (a-1), the structural unit (a-2) and the structural unit (a-3) in the alkali-soluble resin (A) is (a-1) / (a-2) / (a-3)=15-25 / 40-60 / 25-35. <1> ~The above <4> The curable resin composition according to any one of the preceding claims. <6> The alkali-soluble resin (A) contains a structural unit (a-2) having a glass transition temperature of 100 to 180° C. when made into a homopolymer. <1> ~The above <5> The curable resin composition according to any one of the preceding claims. <7> Y in the formula (b-1) 1 and Y 2 are each independently a single bond or a methylene group. <1> ~The above <6> The curable resin composition according to any one of the preceding claims. <8> The above-mentioned film is used for forming an insulating film. <1> ~The above <7> The curable resin composition according to any one of the preceding claims. <9> The above <1> ~The above <8> 2. An insulating cured film obtained by curing the curable resin composition according to any one of claims 1 to 11. <10> The above <1> ~The above <8> 2. An insulating cured film for a touch panel, obtained by curing the curable resin composition according to any one of claims 1 to 11. <11> The above <10> A touch panel comprising the insulating cured film for touch panels according to claim 1. Effect of the Invention
[0013] An object of the present invention is to provide a curable resin composition capable of forming a cured film having excellent chemical resistance, developability, and wrinkle resistance, an insulating cured film and an insulating cured film for a touch panel obtained by curing the composition, and a touch panel including the cured film. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a plan view showing a configuration of one mode of a touch panel according to an embodiment of the present invention. [Diagram 2] 2 is a cross-sectional view taken along the line AA in FIG. [Diagram 3] 1 is an enlarged photograph showing an example of wrinkle evaluation in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. However, the present invention is not limited to this embodiment, and various modifications are possible without departing from the gist of the present invention.
[0016] 《Curable resin composition》 The curable resin composition of the present embodiment includes an alkali-soluble resin (A), a photoreactive monomer (B) represented by the formula (b-1) described later, and a photopolymerization initiator (C). The alkali-soluble resin (A) in the present embodiment is a copolymer including a structural unit (a-1) derived from at least one selected from a compound represented by the formula (a-1α) described later and an unsaturated carboxylic acid having a cyclic skeleton; a structural unit (a-2) having a glass transition temperature of 70 to 200°C when made into a homopolymer; and a structural unit (a-3) derived from an unsaturated compound containing an epoxy group. The curable resin composition of the present embodiment is cured to form a cured film, and when an ITO film is formed on the cured film and then subjected to heat treatment or the like, the cured film generates few wrinkles (i.e., has excellent "wrinkle resistance"), and can form a cured film having excellent chemical resistance and developability as described above.
[0017] <Alkali-soluble resin (A)> In this embodiment, the alkali-soluble resin (A) is a copolymer containing the structural units (a-1), (a-2), and (a-3) described below. The alkali-soluble resin (A) may contain one each of the structural units (a-1), (a-2), and (a-3), or may contain two or more of the same structural units (for example, two types of structural units (a-2)).
[0018] (Structural unit (a-1)) The structural unit (a-1) is a structural unit derived from at least one selected from the compound represented by the following formula (a-1α) and an unsaturated carboxylic acid having a cyclic skeleton. Hereinafter, the compound represented by formula (a-1α) may be referred to as "unsaturated carboxylic acid (a-1α)". Similarly, the unsaturated carboxylic acid having a cyclic skeleton may be referred to as "cyclic unsaturated carboxylic acid (a-1β)". From the viewpoints of wrinkle resistance and developability, the structural unit (a-1) preferably has a glass transition temperature (Tg) of 80 to 300° C., more preferably 100 to 250° C., when made into a homopolymer. The glass transition temperature can be measured by a differential scanning calorimeter (DSC). The weight average molecular weight of the homopolymer measured by DSC is not particularly limited, but an example thereof is about 4,000 to 20,000.
[0019] -Unsaturated carboxylic acid (a-1α)- The unsaturated carboxylic acid (a-1α) is a compound represented by the following formula (a-1α), and is an unsaturated compound having a carboxy group.
[0020] [ka] (In the formula, R 1 ~R 3 each independently represents a hydrogen atom, a methyl group, or a carboxy group; X 1 represents a straight-chain or cyclic aliphatic hydrocarbon group having 1 to 15 carbon atoms which may contain a single bond or an oxygen atom.
[0021] R 1 ~R 3 each independently represents a hydrogen atom, a methyl group, or a carboxy group. X 1represents a straight-chain or cyclic aliphatic hydrocarbon group (divalent bond group) having 1 to 15 carbon atoms which may contain a single bond or an oxygen atom. From the viewpoint of wrinkle resistance, the number of carbon atoms of the aliphatic hydrocarbon group is preferably 1 to 7. These aliphatic hydrocarbon groups may have an -O- structure (a structure containing an oxygen atom: for example, an ester group (-O-), an acid anhydride group (-CO-O-CO-)) in the structure. Examples of the straight-chain aliphatic hydrocarbon group include an alkylene group having 1 to 15 carbon atoms, and an aliphatic hydrocarbon group having 3 to 15 carbon atoms which may contain multiple ester groups or acid anhydride groups (-CO-O-CO-). Examples of the cyclic aliphatic hydrocarbon group include a cycloalkylene group having 3 to 10 carbon atoms, and a cycloalkylene group having 3 to 10 carbon atoms which may contain multiple ester groups or acid anhydride groups. In addition, X 1 X may be an aliphatic hydrocarbon group containing both linear and cyclic moieties. X may have multiple ester or anhydride groups. 1 Examples include -CO-O-CO-CH2-CH2-, -CO-O-CH2-CH2-O-CO-CH2-CH2-, and the like.
[0022] Examples of unsaturated carboxylic acids (a-1α) include methacrylic acid (hereinafter sometimes referred to as "MAA"), acrylic acid, crotonic acid (trans), maleic acid (cis), fumaric acid (trans), citraconic acid (cis), mesaconic acid (trans), itaconic acid, maleic anhydride, citraconic anhydride, itaconic anhydride, and 2-methacryloyloxyethyl hexahydrophthalate. Among these, from the viewpoints of ease of polymerization (hereinafter referred to as polymerizability) with each structural unit (including structural unit a-1) and wrinkle resistance, methacrylic acid, crotonic acid (trans), citraconic acid (cis), mesaconic acid (trans), itaconic acid, and itaconic anhydride are preferred, and methacrylic acid is more preferred.
[0023] -Cyclic unsaturated carboxylic acid (a-1β)- The cyclic unsaturated carboxylic acid (a-1β) is an unsaturated compound having an ethylenically unsaturated bond and a carboxyl group in a cyclic structure, such as an acid anhydride monomer. The acid anhydride monomer has a carboxyl group directly bonded to the main chain, such as maleic anhydride, and becomes a structure similar to methacrylic acid after polymerization.
[0024] The cyclic unsaturated carboxylic acid (a-1β) is preferably an acid anhydride monomer that generates two carboxyl groups by ring-opening after polymerization. In addition, examples of the cyclic unsaturated carboxylic acid (a-1β) include a compound having a double bond in a cyclic skeleton, a compound having an α,β unsaturated carbonyl structure on a cyclic skeleton, and a compound having a condensed bicyclic skeleton.
[0025] Examples of compounds having a double bond in the cyclic skeleton include maleic anhydride, citraconic anhydride, and 2,3-dimethylmaleic anhydride. Examples of compounds having an α,β-unsaturated carbonyl structure on a cyclic skeleton include itaconic anhydride, 2-isopropylidenesuccinic anhydride, (Z)-benzylidenesuccinic anhydride, (E)-benzylidenesuccinic anhydride, (1-phenylethylidene)succinic anhydride, 2-(1-naphthylmethylene)succinic anhydride, benzhydrylidenesuccinic anhydride, and 2-methyl-3-methylenesuccinic anhydride. Examples of the compound having a condensed bicyclic skeleton include 1,2,3,6-tetrahydrophthalic anhydride, 5-norbornene-2,3-dicarboxyl anhydride, and 2,3,4,5-tetrahydrophthalic anhydride. Among the above, as the cyclic unsaturated carboxylic acid (a-1β), 1,2,3,6-tetrahydrophthalic anhydride is preferred from the viewpoint of wrinkle resistance.
[0026] (Structural unit (a-2)) The structural unit (a-2) is a structural unit having a glass transition temperature (Tg) (hereinafter, sometimes simply referred to as "glass transition temperature of structural unit (a-2)") of 70 to 200°C when made into a homopolymer, and has a structure different from that of the structural units (a-1) and (a-3). When the glass transition temperature of the structural unit (a-2) is 70°C or higher, wrinkles are unlikely to occur, and when it is 200°C or lower, developability is excellent. The alkali-soluble resin (A) preferably contains a structural unit (a-2) having a glass transition temperature of 80 to 200°C when made into a homopolymer. Furthermore, the glass transition temperature of the structural unit (a-2) is more preferably 80 to 180°C, and most preferably 100 to 180°C. The glass transition temperature can be measured by a differential scanning calorimeter (DSC) in the same manner as the above-mentioned structural unit (a-1).
[0027] There is no problem with the structural unit (a-2) as long as it satisfies the above conditions. However, for example, from the viewpoint of wrinkle resistance, it is preferable that the structural unit (a-2) is a structural unit derived from at least one selected from the compounds represented by the following formula (a-2α) and the compounds represented by the following formula (a-2β).
[0028] [ka] (In formula (a-2α), R 4 ~R 6 each independently represents a hydrogen atom or a methyl group; R 7 represents a linear, branched or cyclic aliphatic hydrocarbon group having 1 to 12 carbon atoms, or an aromatic group having 6 to 20 carbon atoms. 8 ~R 12 each independently represents a hydrogen atom, a methyl group, an acetyl group, a benzoyl group, an isopropyl group, a tert-butyl group, or a sec-butyl group.
[0029] In formula (a-2α), R 4 ~R 6 Each independently represents a hydrogen atom or a methyl group, and R 4 and R 5 and are hydrogen atoms, and R6 is preferably a methyl group. In formula (a-2α), R 7 represents a linear, branched or cyclic aliphatic hydrocarbon group having 1 to 12 carbon atoms, or an aromatic group having 6 to 20 carbon atoms. When the carbon number is 12 or less, the developability is excellent. The carbon number of the aliphatic hydrocarbon is preferably 1 to 12, and more preferably 1 to 10. Examples of the linear or branched aliphatic hydrocarbon group include an alkyl group having 1 to 12 carbon atoms, a methyl group, a 1-methylethyl group, and a 1,1-dimethylethyl group. Examples of the cyclic aliphatic hydrocarbon group include a cycloalkyl group having 3 to 12 carbon atoms, an isobornyl group, a dicyclopentanyl group, an adamantyl group, and a 3,5-dimethyladamantyl group. The carbon number of the aromatic group is preferably 6 to 20, more preferably 6 to 14, and even more preferably 6 to 12. Examples of the aromatic group include a phenyl group, a naphthyl group, a biphenyl group, and an anthracene group. In addition, R 7 may be an aliphatic hydrocarbon group which simultaneously contains straight chain portions, branched portions and cyclic portions.
[0030] Examples of the compound represented by formula (a-2α) include the following compounds. The temperature in parentheses following the compound indicates the glass transition temperature of the compound. However, this value is a literature value and varies depending on the actual molecular weight and measurement method. Examples of the compound represented by formula (a-2α) include 4-biphenylyl acrylate (100° C.), 3,5-dimethyladamantyl acrylate (106° C.), 2-naphthyl acrylate (85° C.), 3,5-dimethyladamantyl crotonate (159° C.), methyl methacrylate (hereinafter sometimes referred to as “MMA”) (105° C.), 1,1-dimethylethyl methacrylate (118° C.), 1-methyl ... Methyl ethyl (81°C), isobornyl methacrylate (110°C), phenyl methacrylate (110°C), adamantyl methacrylate (141°C), 4-(1,1-dimethylethyl)cyclohexyl methacrylate (83°C), 4-(1,1-dimethylethyl)phenyl methacrylate (98°C), 3,3-dimethyl-1-butyl methacrylate (108°C), 3,3,5-trimethylhexyl methacrylate (12 5°C), 2,3-xylyl methacrylate (125°C), dicyclopentanyl methacrylate (also known as dicyclopentanyl methacrylate) (175°C), and 3,5-dimethyladamantyl methacrylate (196°C). From the viewpoint of wrinkle resistance, 4-biphenylyl acrylate, 3,5-dimethyladamantyl acrylate, 3,5-dimethyladamantyl crotonate, methyl methacrylate, and 1,1-dimethylethyl, isobornyl methacrylate, phenyl methacrylate, adamantyl methacrylate, 3,3-dimethyl-1-butyl methacrylate, 3,3,5-trimethylhexyl methacrylate, 2,3-xylyl methacrylate, dicyclopentanyl methacrylate, and 3,5-dimethyladamantyl methacrylate are preferred, and methyl methacrylate and dicyclopentanyl methacrylate are more preferred.
[0031] In formula (a-2β), R 8 ~R 12 Each of R independently represents a hydrogen atom, a methyl group, an acetyl group, a benzoyl group, an isopropyl group, a tert-butyl group, or a sec-butyl group, and from the viewpoint of wrinkle resistance, it is preferable that R has an acetyl group or a tert-butyl group. 8 ~R 12 may further be substituted with a substituent such as an alkyl group.
[0032] Examples of the compound represented by formula (a-2β) include 4-acetylstyrene (116°C), 4-benzoylstyrene (98°C), 5-(1,1-dimethylethyl)-2-methylstyrene (87°C), 4-(1-methylpropyl)styrene (86°C), 4-(1,1-dimethylethyl)styrene (126°C), 2,5-diisopropylstyrene (168°C), 2,4-dimethylstyrene (112°C), and 2,5-dimethylstyrene (143°C). From the viewpoint of wrinkle resistance, 4-acetylstyrene, 4-(1,1-dimethylethyl)styrene, 2,5-diisopropylstyrene, 2,4-dimethylstyrene, and 2,5-dimethylstyrene are preferred, and 4-(1,1-dimethylethyl)styrene is more preferred. As described above, the temperature in parentheses following the compound indicates the glass transition temperature of the compound, but the value is a literature value and varies depending on the actual molecular weight and measurement method.
[0033] (Structural unit (a-3)) The structural unit (a-3) is a structural unit derived from an unsaturated compound containing an epoxy group. The structural unit derived from an unsaturated compound containing an epoxy group can be appropriately selected from the unsaturated compounds containing an epoxy group (or structural units derived therefrom) that have been used in various photosensitive resin compositions in the past. From the viewpoint of improving wrinkle resistance and reactivity with other structural units, the structural unit (a-3) has a glass transition temperature, when made into a homopolymer, of preferably 20 to 100° C., more preferably 30 to 90° C., and particularly preferably 30 to 80° C. The glass transition temperature can be measured by a differential scanning calorimeter (DSC). The molecular weight of the epoxy group-containing unsaturated compound is preferably 100 to 1,000, more preferably 100 to 500, and particularly preferably 100 to 300, from the viewpoint of reactivity with other structural units.
[0034] Examples of the epoxy group-containing unsaturated compound include unsaturated compounds having an epoxy structure in a cyclic structure, such as an alicyclic epoxy group, and unsaturated compounds not having an alicyclic epoxy group. Of these, unsaturated compounds having an epoxy structure in a cyclic structure, such as an alicyclic epoxy group, are preferred.
[0035] In the unsaturated compound having an alicyclic epoxy group, the alicyclic group constituting the alicyclic epoxy group may be monocyclic or polycyclic. Examples of the monocyclic alicyclic group include a cyclopentyl group and a cyclohexyl group. Examples of the polycyclic alicyclic group include a norbornyl group, an isobornyl group, a tricyclononyl group, a tricyclodecyl group, and a tetracyclododecyl group. Examples of the unsaturated compound having an epoxy group include the unsaturated compounds containing an epoxy group described in paragraphs 0015 to 0024 of JP 2013-228662 A. Specifically, glycidyl methacrylate, 2-methylglycidyl methacrylate, 3,4-epoxybutyl methacrylate, 6,7-epoxyheptyl methacrylate, and 3,4-epoxycyclohexylmethyl methacrylate (3,4-epoxycyclohexylmethyl methacrylate) are preferred, and 3,4-epoxycyclohexylmethyl methacrylate is more preferred from the viewpoint of chemical resistance.
[0036] (Composition ratio) From the viewpoint of achieving both chemical resistance and wrinkle resistance, the contents (mol %) of the structural units (a-1), (a-2) and (a-3) in the alkali-soluble resin (A) are preferably (a-1) / (a-2) / (a-3)=15-25 / 40-60 / 25-35, more preferably 15-23 / 45-60 / 25-32, and particularly preferably 15-21 / 50-60 / 25-29.
[0037] (Other building blocks) The alkali-soluble resin (A) may contain other structural units that do not fall into any of the above-mentioned structural units (a-1) to (a-3). Examples of other structural units include benzyl methacrylate, 1,3-bis(methacryloyloxy)-2-propanol, 2-methacryloyloxyethyl isocyanate, and 2-hydroxyethyl methacrylate. The content (mol %) of other structural units in the alkali-soluble resin (A) is preferably from 0 to 20 mol %, more preferably from 0 to 10 mol %, from the viewpoint of achieving both chemical resistance and wrinkle resistance.
[0038] (molecular weight) The weight average molecular weight of the alkali-soluble resin (A) is preferably 5000 to 20000, more preferably 6000 to 17000, and particularly preferably 6500 to 14000. The molecular weight of the alkali-soluble resin (A) can be measured by gel permeation chromatography (manufactured by Tosoh Corporation, product number: HLC-8120, column: two columns, G-5000HXL and G-3000HXL, connected together, detector: RI, mobile phase: tetrahydrofuran).
[0039] (glass transition temperature) From the viewpoint of wrinkle resistance, the glass transition temperature of the alkali-soluble resin (A) is preferably from 50 to 200° C., more preferably from 70 to 170° C., and particularly preferably from 80 to 140° C. The glass transition temperature can be measured by a differential scanning calorimeter (DSC).
[0040] (Specific examples) Specific examples of the alkali-soluble resin (A) include the following polymers: In the table below, A3 contains benzyl methacrylate as another structural unit.
[0041] [Table 1]
[0042] (Content) The content of the alkali-soluble resin (A) in the curable resin composition of the present embodiment is not particularly limited, but from the viewpoint of chemical resistance, it is preferably 30 to 80 mass %, more preferably 40 to 70 mass %, and particularly preferably 50 to 60 mass % based on the total solid content in the composition. Throughout this specification, the term "total solid content" refers to all components in the resin composition other than the solvent.
[0043] <Other polymers> The curable resin composition of the present embodiment may contain other polymers other than the alkali-soluble resin (A). The other polymers are not particularly limited, and examples thereof include polymers containing any two of the above-mentioned structural units (a-1) to (a-3). Examples of the other polymers include the following polymers.
[0044] [Table 2]
[0045] The content of the other polymer in the curable resin composition of the present embodiment is not particularly limited, but from the viewpoint of obtaining the effects of including the other polymer without significantly impairing the chemical resistance, etc. of the cured film, the content is preferably 5 to 30 parts by mass, and more preferably 10 to 20 parts by mass, relative to 100 parts by mass of the alkali-soluble resin (A).
[0046] <Photoreactive monomer (B)> The photoreactive monomer (B) is a compound represented by the following formula (b-1), and is a compound having two ethylenically unsaturated groups in the molecule.
[0047] [ka] (In formula (b-1), R 13 ~R 14 each independently represents a hydrogen atom or a methyl group; Y 1 ~Y 2each independently represents a single bond or a linear or branched aliphatic hydrocarbon group having 1 to 6 carbon atoms; X 2 represents an aliphatic hydrocarbon group or an aromatic group having a cyclic skeleton.
[0048] In formula (b-1), R 13 ~R 14 each independently represents a hydrogen atom or a methyl group, and from the viewpoint of photoreactivity, a hydrogen atom is preferred. Y 1 ~Y 2 each independently represents a single bond, or a linear or branched aliphatic hydrocarbon group (divalent bonding group) having 1 to 6 carbon atoms. From the viewpoint of chemical resistance, the number of carbon atoms in the aliphatic hydrocarbon group is preferably 1 to 3. Examples of linear or branched aliphatic hydrocarbon groups include alkylene groups having 1 to 6 carbon atoms, 1-methylethyl groups, 1-methylpropyl groups, 2-methylpropyl groups, and 1,1-dimethylethyl groups. Y 1 and Y 2 is preferably a single bond or a methylene group. X 2 represents an aliphatic hydrocarbon group or aromatic group (divalent linking group) having a cyclic skeleton. From the viewpoint of chemical resistance, X 2 The number of carbon atoms in is preferably 5 to 20, and more preferably 6 to 12. Examples of the aliphatic hydrocarbon having a cyclic skeleton include a divalent linking group consisting of a cyclohexane ring, a cyclodecane ring, a tricyclodecane ring, an adamantane ring, a norbornane ring, or a decalin ring, and examples of the aromatic group having a cyclic skeleton include a divalent linking group consisting of a benzene ring or a naphthalene ring. 2 From the viewpoint of chemical resistance, a divalent linking group consisting of a cyclohexane ring, a benzene ring, a cyclodecane ring, adamantane ring, or a norbornane ring is preferable, and a divalent linking group consisting of a benzene ring, an adamantane ring, or a tricyclodecane ring is more preferable.
[0049] Examples of the photoreactive monomer (B) include A-DCP (tricyclodecane dimethanol diacrylate), 1,4-benzenediol diacrylate, and 1,3-adamantanediol diacrylate, and from the viewpoint of chemical resistance, tricyclodecane dimethanol diacrylate is preferred.
[0050] The content of the photoreactive monomer in the curable resin composition of the present embodiment is not particularly limited. For example, from the viewpoint of chemical resistance, the content is preferably 30 to 80 parts by mass, more preferably 40 to 70 parts by mass, and particularly preferably 50 to 60 parts by mass, relative to 100 parts by mass of the alkali-soluble resin (A).
[0051] In addition, the curable resin composition of the present embodiment may contain a photoreactive monomer other than the photoreactive monomer (B). The other photoreactive monomer is not particularly limited, but may be, for example, a compound having three or more ethylenically unsaturated groups in the molecule. Examples of such compounds include, for example, trimethylolpropane triacrylate and pentaerythritol triacrylate. When the curable resin composition of the present embodiment contains the photoreactive monomer (B) and another photoreactive monomer, from the viewpoint of chemical resistance, the content of the photoreactive monomer (B) relative to the total amount of the photoreactive monomers in the curable resin composition is preferably 75 mass% or more, and more preferably 80 mass% or more.
[0052] (Photopolymerization initiator (C)) The curable resin composition of the present embodiment contains a photopolymerization initiator (C). The photopolymerization initiator (C) is not particularly limited, but for example, a photopolymerization initiator that generates radicals that polymerize ethylenically unsaturated groups by ultraviolet to visible light can be suitably used.
[0053] The photopolymerization initiator is not particularly limited, and examples thereof include acetophenones such as acetophenone, 2,2'-diethoxyacetophenone, p-dimethylacetophenone, p-dimethylaminopropiophenone, dichloroacetophenone, trichloroacetophenone, and p-tert-butylacetophenone; 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one; 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholinophenyl)-butan-1-one; α-aminoketone photoinitiators such as 1-[4-(phenylthio)-2-(O-benzoyloxime)], 1,2-octanedione 1-[4-(phenylthio)-2-(O-benzoyloxime)], ethanone-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime), 1-[9-ethyl-6-benzoyl-9.H.-carbazol-3-yl]-octanedione-1-[4-(phenylthio)-2-(O-benzoyloxime)], ... 1-[9-ethyl-6-(2-methylbenzoyl)-9.H-carbazol-3-yl]-ethan-1-one oxime-O-benzoate, 1-[9-n-butyl-6-(2-ethylbenzoyl)-9.H-carbazol-3-yl]-ethan-1-one oxime-O-benzoate, ethanone-1-[9-ethyl-6-(2-methyl-4-tetrahydrofuranylbenzoyl)-9.H-carbazol-3-yl]-1-(O-acetate oxime), ethanone-1-[9-ethyl-6-(2-methyl-4-tetrahydropyranylbenzoyl)-9.H.-carbazol-3-yl]-1-(O-acetyloxime), ethanone-1-[9-ethyl-6-(2-methyl-5-tetrahydrofuranylbenzoyl)-9.H.-carbazol-3-yl]-1-(O-acetyloxime), ethanone-1-[9-ethyl-6-{2-methyl-4-(2,2-dimethyl-1,3-dioxolanyl)methoxybenzoyl}-9.H.oxime ester photopolymerization initiators such as [O-carbazol-3-yl]-1-(O-acetyloxime), benzophenones such as benzophenone, 2-chlorobenzophenone, and p,p'-bisdimethylaminobenzophenone; benzoin ethers such as benzil, benzoin, benzoin methyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; sulfur compounds such as benzil dimethyl ketal, thioxanthone, 2-chlorothioxanthone, 2,4-diethylthioxanthone, 2-methylthioxanthone, and 2-isopropylthioxanthone, 2-ethylanthraquinone, octamethylanthraquinone, and 1,2-benzo Examples of the photopolymerization initiator include anthraquinones such as anthraquinone and 2,3-diphenylanthraquinone; triazines such as 2,4-trichloromethyl-(4'-methoxyphenyl)-6-triazine, 2,4-trichloromethyl-(4'-methoxynaphthyl)-6-triazine, 2,4-trichloromethyl-(piperonyl)-6-triazine, and 2,4-trichloromethyl-(4'-methoxystyryl)-6-triazine; organic peroxides such as azobisisobutyronitrile, benzoyl peroxide, and cumene peroxide; and thiol compounds such as 2-mercaptobenzimidazole, 2-mercaptobenzoxazole, and 2-mercaptobenzothiazole. These photopolymerization initiators may be used alone or in combination of two or more.
[0054] The content of the photopolymerization initiator (C) in the curable resin composition of the present embodiment is not particularly limited. For example, from the viewpoints of photoreactivity and storage stability, the content is preferably 0.1 to 30 parts by mass, more preferably 1 to 20 parts by mass, and particularly preferably 2 to 15 parts by mass relative to 100 parts by mass of the alkali-soluble resin (A).
[0055] <Method for producing curable resin composition> The curable resin composition of the present embodiment contains an alkali-soluble resin (A), a photoreactive monomer (B), a photopolymerization initiator (C), and can be prepared by stirring and mixing other ingredients such as a solvent.
[0056] (solvent) In the present embodiment, the solvent can be appropriately selected from known solvents depending on the desired purpose. Examples of the solvent include cyclopentanone, diethylene glycol ethyl methyl ether, acetylacetone, methanol, ethanol, ethyl cellosolve, ethyl cellosolve acetate, methyl cellosolve, methyl cellosolve acetate, diglyme, cyclohexanone, ethylbenzene, xylene, isoamyl acetate, n-amyl acetate, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether, propylene glycol monoethyl ether acetate, diethylene glycol, diethylene glycol monomethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether, diethylene glycol Examples of the polyethylene glycol monoethyl ether acetate include diethylene glycol monobutyl ether, ethylene glycol monobutyl ether acetate, triethylene glycol, triethylene glycol monomethyl ether, triethylene glycol monomethyl ether acetate, triethylene glycol monoethyl ether, triethylene glycol monoethyl ether acetate, liquid polyethylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monomethyl ether acetate, dipropylene glycol monoethyl ether, dipropylene glycol monoethyl ether acetate, lactate esters, methyl methoxypropionate, and ethyl ethoxypropionate.
[0057] The solvents may be used alone or in combination of two or more. In addition, the content of the solvent in the curable resin composition of the present embodiment is not particularly limited, but for example, from the viewpoint of storage stability and coatability, it is preferable to use a solvent so that the total solid content (total mass of components other than the solvent in the composition) concentration is preferably 1 to 40 mass%, more preferably 5 to 40 mass%, and particularly preferably 10 to 30 mass%. By setting the solid content ratio within the above range, the viscosity of the curable resin composition can be made appropriate, and the coatability when applying it to a substrate or the like to form a film is particularly improved.
[0058] The curable resin composition of the present embodiment may also contain various additives such as inorganic fine particles, adhesion promoter additives, surfactants, storage stabilizers, leveling agents, light stabilizers, and antioxidants, if necessary. Examples of these additives include those described in JP-A-2012-215833. In addition, a silane coupling agent or the like may be used to increase the adhesion between the substrate and the coating film.
[0059] <Insulating cured film> The use of the curable resin composition of the present embodiment is not particularly limited, but it can be used, for example, as an insulating cured film for a touch panel. The insulating cured film for a touch panel can be formed by forming a coating film of the curable resin composition on a substrate such as a glass substrate, ITO, a metal film, or an organic film using various application methods such as spin coating, casting coating, roll coating, or roll transfer coating, and then curing the coating film.
[0060] Specifically, the cured film of the present embodiment can be formed by applying the curable resin composition onto a substrate such as a glass substrate and curing it by irradiating it with light. The cured film of the present embodiment can also be patterned by irradiating it with light through a mask, developing it, and then heat-treating it as necessary.
[0061] The insulating cured film can be used for any application such as an insulating film application, a protective film application, a flat film application, etc. The insulating cured film using the curable resin composition of the present embodiment can be suitably used in particular as a protective film for a touch panel or an insulating film for a touch panel.
[0062] Furthermore, the insulating cured film of the present embodiment may be used not only as a so-called permanent film that is maintained in devices such as touch panels, but also as a resist film used when patterning an ITO film on a glass substrate.
[0063] <Touch panel> As described above, the curable resin composition of the present embodiment and the insulating cured film using the same can be suitably used as an insulating film for a touch panel. Hereinafter, the insulating cured film of the present embodiment and the insulating film for a touch panel may be collectively referred to simply as the "cured film of the present embodiment". When the cured film of the present embodiment is used for an insulating film, an ITO film may be formed on the cured film, and then a heat treatment or the like may be performed. Even after such a treatment, the cured film of the present embodiment has few wrinkles on the contact surface with the ITO film, and is less likely to inhibit transparency. In addition, the cured film of the present embodiment has excellent developability (adhesion between the glass substrate and the ITO film after the insulating cured film is removed) and chemical resistance (inhibitory effect of reducing the adhesion between the insulating film and the ITO film when exposed to chemicals used in the manufacturing process), so that a touch panel equipped with the cured film of the present embodiment has excellent productivity.
[0064] The touch panel of the present embodiment may be of any of a resistive type, a capacitive type, an ultrasonic type, and an optical type, but is preferably a capacitive type touch panel. The capacitive touch panel uses, for example, glass with an ITO film as a substrate, and provides an insulating film or a protective film in the laminated structure (for example, between electrodes) to prevent erroneous recognition of the touched position. When the touch panel of the present embodiment is a capacitive touch panel, the cured film of the present embodiment can be used, for example, as an insulating film, a protective film, or both in the laminated structure.
[0065] Further, touch panels can be divided into a two-sided structure in which an X electrode is disposed on one side of an insulating film and a Y electrode is disposed on the other side, and a one-sided structure in which an X electrode and a Y electrode are formed on the same plane. The touch panel of this embodiment may have either a two-sided or one-sided structure, but is preferably a touch panel with a one-sided structure. In a one-sided touch panel structure, the X electrodes and the Y electrodes are electrically separated. In this case, the electrode patterns can be classified into, for example, an island type pattern, a through-hole type pattern, and the like. For example, in the case of an island type pattern, or in a one-sided touch panel structure, the separated electrodes are electrically connected to each other by a member called a jumper section. In addition, a transparent electrode such as an ITO film is used in the electrode jumper section, but when the jumper section connects the separated Y electrodes to each other, for example, an insulating layer is provided under the jumper section to maintain insulation with the X electrodes. In addition, an insulating film (protective film) is usually formed uniformly on each electrode arranged in a one-sided type. Therefore, when the touch panel of this embodiment has a one-sided touch panel structure, the touch panel of this embodiment can use, for example, the cured film of this embodiment as an insulating film formed on an electrode, an insulating layer formed under a jumper portion, or both.
[0066] Furthermore, when a touch panel is incorporated into a liquid crystal display device, it can be classified into an out-cell structure, an on-cell structure, and an in-cell structure according to the installation location. In the on-cell structure and the in-cell structure, the touch panel is incorporated into the liquid crystal panel, and in the out-cell structure, the touch panel is incorporated outside the liquid crystal panel. In the on-cell structure, the touch panel is installed between the polarizing plate on the observation direction side and a liquid crystal laminate (a laminate composed of a pair of base glasses and a liquid crystal layer interposed therebetween). In the in-cell structure, the liquid crystal layer of the liquid crystal laminate has a touch panel function. The touch panel of the present embodiment can be applied to any structure, but is preferably used in, for example, an on-cell structure.
[0067] Hereinafter, one aspect of the touch panel of the present embodiment will be described with reference to the drawings. Fig. 1 is a plan view showing the configuration of one aspect of the touch panel of the present embodiment. As shown in Fig. 1, when the touch panel of the present embodiment is a single-sided touch panel, ITO (indium tin oxide) electrodes (X1 to X4, Y1 to Y3) are formed on a glass substrate 10.
[0068] The material of the glass substrate 10 is not particularly limited, but may be, for example, a glass plate such as soda-lime glass, low-alkali borosilicate glass, or non-alkali aluminoborosilicate glass. Also, instead of a glass substrate, a plastic plate or film made of polyethylene terephthalate (PET), triacetyl cellulose (TAC), polymethyl methacrylate (PMMA), polycarbonate (PC), or the like may be used.
[0069] The ITO electrodes (X1 to X4, Y1 to Y3) are transparent electrodes. In this embodiment, ITO is used as the material of the transparent electrodes, but there is no particular limitation as long as it can be disposed on the substrate surface. In addition to ITO, for example, inorganic conductive materials such as ZnO (zinc oxide) and organic conductive materials such as PEDOT / PSS (polyethylenedioxythiophene / polystyrenesulfonic acid), polyaniline, and polypyrrole can also be used. These materials may be used alone or in combination of two or more. 1 and 2, a metal thin film having a function as metal wiring may be used as an underlying layer or in place of a transparent electrode in each electrode and jumper section 12. Metal materials such as Mo (molybdenum), Al (aluminum), Ag (silver), and Pd (palladium) can be used for the metal thin film, and it is preferable to use at least one of Mo and Al.
[0070] As shown in Fig. 1, the ITO electrodes X1 to X4 are arranged in the direction of the arrow X in Fig. 1. The ITO electrodes X1 to X4 are continuously connected to adjacent electrodes in the X direction via connecting parts formed of ITO films, and are electrically connected in the X direction. Usually, the ITO electrodes X1 to X4 are continuously formed integrally with each connecting part when the electrodes are formed. 1, and the ITO electrodes Y1 to Y3 are separated from adjacent electrodes, but are electrically connected to adjacent electrodes in the Y direction via jumper sections 12. The jumper sections 12 can be made of the same material as the transparent electrodes, such as ITO. An insulating film 14 is interposed between the jumper sections 12 and the connection sections of the ITO electrodes X at the bottom in the thickness direction. Hereinafter, the group of electrodes electrically connected in the X direction will be referred to as the "X electrodes," and the group of electrodes electrically connected in the Y direction will be referred to as the "Y electrodes." As shown in Figure 1, in a single-sided touch panel, the X electrodes are arranged along the Y direction, and the Y electrodes are arranged along the X direction.
[0071] Next, the cross-sectional structure of the touch panel in this embodiment will be described with reference to FIG. 2. FIG. 2 is a cross-sectional view taken along the line AA in FIG. 1. As shown in FIG. 2, an insulating film 14 and a connection portion X34 of the ITO electrodes X3 and X4 are interposed between the ITO electrodes Y1 and Y2. The ITO electrodes Y1 and Y2 are electrically connected by the jumper portion 12 as described above. In addition, a part of the insulating film 14 extends between the jumper portion 12 and the connection portion X34 at the lower part in the thickness direction of the jumper portion 12, thereby maintaining insulation between the jumper portion 12 and the connection portion X34. In addition, an insulating protective layer 16 is provided on the upper side of the ITO electrodes Y1 and Y2 and the jumper portion 12 in the thickness direction.
[0072] As described above, the insulating cured film using the curable resin composition of the present embodiment has excellent chemical resistance. Therefore, for example, when the cured film of the present embodiment is used as the insulating film 14, the adhesive strength at the interface between the insulating film 14 and the ITO film (ITO film / insulating film interfaces K1, K5 in FIG. 2) is excellent due to the chemicals used during the manufacturing process (e.g., during etching of the ITO film). Similarly, when the cured film of the present embodiment is used as the insulating protective layer 16, the adhesive strength at the interface between the insulating protective layer 16 and the ITO film (ITO film / protective film interface K2 in FIG. 2) is excellent. Furthermore, when the cured film of the present embodiment is used as the insulating film 14, it is possible to reduce the amount of wrinkles that occur during the heat treatment process for forming the jumper portion 12 on the insulating film 14. From this viewpoint, when the cured film of the present embodiment is used as the insulating film 14, the influence on the transparency of the insulating film 14 and therefore on the transparency of the touch panel is minimized, and the touch panel can be manufactured with good productivity.
[0073] In this embodiment, the cured film of this embodiment is used for at least one of the insulating film 14 and the insulating protective layer 16. However, the other may be formed using a known material that has been conventionally used for insulating films and protective films, but it is preferable that both the insulating film 14 and the insulating protective layer 16 are the cured film of this embodiment.
[0074] In the above-mentioned touch panel, the method for forming the cured film of the present embodiment is not particularly limited, but for example, a coating film can be formed on the lower layer (for example, the glass substrate 10 and ITO electrode for the insulating film 14, or the ITO electrode for the insulating protective layer 16, etc.) by a coating method such as spray coating, spin coating, slit die coating, roll coating, bar coating, etc. In this case, the dry film thickness of the coating film is not particularly limited, but for example, in the case of the insulating protective layer 16, it is preferably 0.5 to 20 μm, and more preferably 1.0 to 10 μm. Similarly, in the case of the insulating film 14, the dry film thickness is preferably 0.2 to 10 μm, and more preferably 0.5 to 5 μm. In addition, if necessary, the coating film can be exposed through a mask having a predetermined pattern provided in contact with or without contact with the coating film. The type of light during exposure is not particularly limited, and examples include visible light, ultraviolet light, far infrared light, electron beams, X-rays, etc., among which ultraviolet light is preferred. The illuminance of the light is not particularly limited, but is preferably 5 to 150 mW / cm at 365 nm. 2 is preferably 15 to 35 mW / cm 2 It is particularly preferred that: Thereafter, the uncured portions are removed to form a desired pattern by immersing the film in an aqueous alkaline developer such as sodium carbonate, sodium hydroxide, or potassium hydroxide, or by spraying the developer onto the film using a spray or the like, as necessary. Furthermore, in order to promote polymerization of the photosensitive composition and harden the film, heating (post-baking) can be performed as necessary.
[0075] Furthermore, for example, when the jumper section 12 is formed, first, a patterned X electrode is formed on the glass substrate 10, and then a curable resin composition is applied to the glass substrate 10 and the surface of the X electrode, and the curable resin composition is exposed and developed using a mask capable of forming an insulating film 14. Then, a patterned insulating film 14 is formed including a portion extending to the lower part of the jumper section 12 in the thickness direction, and then ITO or the like is deposited on the substrate by PVD or the like to form an ITO film on the insulating film 14 and on the glass substrate 10 from which the curable resin composition has been removed, thereby forming the Y electrode and the jumper section 12. Therefore, when the curable resin composition of this embodiment is used as a curable resin composition used for resist application in forming the X electrode and in forming the insulating film 14, the adhesive strength of the interface between the glass substrate 10 and each electrode (glass substrate / ITO film interface K4 in FIG. 2) is excellent. EXAMPLES
[0076] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.
[0077] [Examples and Comparative Examples] The components were mixed according to the composition shown in the following table to prepare a curable resin composition. The mixing was performed at room temperature while blocking ultraviolet rays to prevent the initiation of polymerization reaction.
[0078] [Table 3]
[0079] In the above table, the components used were those shown in the following table.
[0080] [Table 4] Incidentally, A3 contains benzyl methacrylate as another structural unit.
[0081] Evaluation The curable compositions of the Examples and Comparative Examples obtained above were evaluated. The results are shown in the following table.
[0082] (Chemical resistance test) The obtained curable resin composition was applied onto a substrate having an ITO film by spin coating, and prebaked on a hot plate at 80°C for 100 seconds to form a coating film. The coating was then exposed to light from an ultra-high pressure mercury lamp at 50 mJ / cm 2 Irradiated (illuminance at 365 nm: 30 mW / cm 2 The resist was then developed with a 0.3% aqueous solution of sodium carbonate for 50 seconds and heated at 150° C. for 30 minutes to produce a substrate with a cured film having a thickness of 2.0 μm.
[0083] The obtained substrate with the cured film was immersed in a 3.6 mass% aqueous oxalic acid solution for about 120 seconds at 41° C. After immersion, the substrate was washed with water and further immersed in an amine solution (monoethanolamine / diethylene glycol monobutyl ether=35 / 65 (mass%)) at 80° C. for about 60 seconds. After immersion, the substrate with the cured film was washed with water and dried, and then the surface of the cured film was cross-cut using a cutter knife (1 mm x 1 mm x 100 squares). Thereafter, cellophane tape was applied to the cut surface, and then the cellophane tape was peeled off. The surface of the cured film on the substrate was observed under a stereomicroscope to count the number of squares where the cured film remained without peeling off, and the adhesion (chemical resistance) of the cured film after immersion in chemicals was evaluated according to the following criteria. Moreover, for Examples 1 to 3, when the same test was carried out on the substrates in which the MAM film was used instead of the ITO film, all of them were rated "A".
[0084] [standard] A: 95 or more squares remain without peeling off the cured film B: The number of squares that remain without peeling off the cured film is 85 to 95. C: The number of squares that remain without peeling off the cured film is 65 to 85. D: The number of squares that remain without peeling off the cured film is 35 to 65. E: Less than 35 squares remain without peeling off the cured film
[0085] (Developability test) The obtained curable resin composition was applied onto a glass substrate by spin coating, prebaked on a hot plate at 80°C for 100 seconds to form a coating film, and developed using a 0.3% aqueous sodium carbonate solution for 50 seconds. After that, the substrate was heated at 150°C for 30 minutes to prepare a substrate.
[0086] The obtained substrate was subjected to an ITO sputtering process according to the following method: Next, the substrate on which the ITO film was formed was subjected to an annealing process (150° C., 30 minutes) to obtain a substrate on which an ITO film was formed.
[0087] [Table 5]
[0088] Next, at the portion where the ITO film was formed directly on the glass substrate, the surface of the cured film was cross-cut with a cutter knife (1 mm×1 mm×100 squares). Thereafter, cellophane tape was applied to the cut surface, and then the cellophane tape was peeled off. The surface of the cured film on the substrate was observed under a stereomicroscope to count the number of squares where the cured film remained without peeling off, and the adhesion (developability) between the glass substrate and the ITO film at the site where the curable resin composition was removed was evaluated according to the following criteria.
[0089] [standard] A: 95 or more squares remain without peeling off the cured film B: The number of squares that remain without peeling off the cured film is 85 to 95. C: The number of squares that remain without peeling off the cured film is 65 to 85. D: The number of squares that remain without peeling off the cured film is 35 to 65. E: Less than 35 squares remain without peeling off the cured film
[0090] (Check for wrinkles) The obtained curable resin composition was applied onto a glass substrate by spin coating, and prebaked on a hot plate at 80°C for 100 seconds to form a coating film. The coating film was then exposed to light from an ultra-high pressure mercury lamp at 50 mJ / cm using a patterned mask. 2 Irradiated (illuminance at 365 nm: 30 mW / cm 2 ). The exposure was performed with a gap (exposure gap) between the mask and the substrate of 100 μm. The non-exposed areas were removed by developing with a 0.3% aqueous sodium carbonate solution for 50 seconds. After that, the substrate was heated at 150°C for 30 minutes to produce a substrate with a patterned cured film having a thickness of 2 μm. The obtained substrate was subjected to an ITO sputtering process in the same manner as in the above-mentioned developability test. Next, the substrate on which the ITO film was formed was subjected to an annealing process (150°C, 30 minutes) to obtain a substrate on which an ITO film was formed.
[0091] The surface of the cured film on the substrate on which the ITO film was formed was observed through the ITO film using a stereomicroscope (magnification: 40x), and the degree of wrinkles on the surface of the cured film was evaluated according to the following criteria. Sample images of the following evaluations A, C, and E are shown in Figure 3. [standard] A: No wrinkles were observed. B: Almost no wrinkles were observed. C: Wrinkles were observed in some areas. D: Wrinkles were observed over a wide area. E: Wrinkles were observed over the entire surface.
[0092] [Table 6]
[0093] The disclosure of Japanese Patent Application No. 2019-111325, filed on June 14, 2019, is incorporated herein by reference in its entirety. In addition, all publications, patent applications, and technical standards mentioned in the specification are herein incorporated by reference to the same extent as if each individual publication, patent application, and technical standard was specifically and individually indicated to be incorporated by reference. [Explanation of symbols]
[0094] 10: glass substrate, 12: jumper portion, 14: insulating film, 16: insulating protective layer, X1 to X4, Y1 to Y4: ITO electrodes, X34: connection portion, K1, K5: ITO film / insulating film interface, K2: ITO film / protective film interface, K3, K4: glass substrate / ITO film interface
Claims
1. An alkali-soluble resin (A) which is a copolymer containing a compound represented by the following formula (a-1α) and a structural unit (a-1) derived from at least one selected from unsaturated carboxylic acids having a cyclic skeleton; a structural unit (a-2) having a glass transition temperature of 70 to 200° C. when made into a homopolymer; and a structural unit (a-3) derived from an unsaturated compound containing an epoxy group; A photoreactive monomer (B) represented by the following formula (b-1), A photopolymerization initiator (C); Including, The structural unit (a-2) is derived from a compound represented by the following formula (a-2α): The content of structural units other than the structural units (a-1) to (a-3) is 0 to 20 mol %. 【Chemistry 1】 (In the formula, R 1 ~R 3 each independently represents a hydrogen atom, a methyl group, or a carboxy group; X 1 represents a straight-chain or cyclic aliphatic hydrocarbon group having 1 to 15 carbon atoms which may contain a single bond or an oxygen atom. 【Chemistry 2】 (In formula (b-1), R 13 ~R 14 each independently represents a hydrogen atom or a methyl group; Y 1 ~Y 2 each independently represents a single bond or a linear or branched aliphatic hydrocarbon group having 1 to 6 carbon atoms; X 2 represents an aliphatic hydrocarbon group or an aromatic group having a cyclic skeleton. 【Chemistry 3】 (In formula (a-2α), R 4 ~R 6 each independently represents a hydrogen atom or a methyl group; R 7 represents a linear or branched aliphatic hydrocarbon group having 1 to 12 carbon atoms.
2. 2. The curable resin composition for insulating cured films for touch panels according to claim 1, wherein the content of the photoreactive monomer (B) relative to the total amount of the photoreactive monomers in the curable resin composition is 75 mass% or more.
3. The curable resin composition for forming an insulating cured film for a touch panel according to claim 1 or 2, wherein the weight average molecular weight of the alkali-soluble resin (A) is 5,000 to 20,000.
4. The content (mol%) of the structural unit (a-1), the structural unit (a-2) and the structural unit (a-3) in the alkali-soluble resin (A) is (a-1) / (a-2) / (A-3)=15-25 / 40-60 / 25-35. The curable resin composition for an insulating cured film for a touch panel according to any one of claims 1 to 3.
5. The alkali-soluble resin (A) contains a structural unit (a-2) having a glass transition temperature of 100 to 180° C. when made into a homopolymer. The curable resin composition for insulating cured films for touch panels according to any one of claims 1 to 4.
6. Y in the formula (b-1) 1 and Y 2 The curable resin composition for an insulating cured film for a touch panel according to any one of claims 1 to 5, wherein each of the groups independently represents a single bond or a methylene group.
7. 7. An insulating cured film for a touch panel, obtained by curing the curable resin composition for an insulating cured film for a touch panel according to claim 1.
8. A touch panel comprising the insulating cured film for a touch panel described in claim 7.
Citation Information
Patent Citations
Radiation sensitive resin composition for forming protective film of touch panel, and forming method thereof
JP2010027033A
Touch panel substrate and method of manufacturing the same
JP2012088836A
Curable resin composition which contains alicyclic epoxy group, method for producing the same, and cured product thereof
JP2013001749A
Heat conductive sheet and method for manufacturing heat conductive sheet
JP2015003953A
Touch panel
JP2017041204A